Service life extension of concrete tunnels by means of impressed current cathodic protection (ICCP) – Case study: Throne tunnel (Brussels) - Van Belleghem Bjorn; Maes Mathias (MATEC Web of Conferences, 2025)
Impressed current cathodic protection (ICCP) was adopted as a durable repair strategy to extend the service life of a 55-year old reinforced concrete tunnel roof slab, owing to a widespread risk for damage due to reinforcement corrosion. An ICCP system with TiMMO ribbon anodes in a shotcrete overlay was designed, divided into 24 zones. An 85 m2 test area was installed to verify the design and assess the performance during a 43-day trial period. A cathodic current density of 14 mA/m² steel was found to be sufficient to obtain an adequate protection of the steel reinforcement, demonstrated by decay measurements according to the European standard EN ISO 12696:2022.